Amarna sunset : Nefertiti, Tutankhamun, Ay, Horemheb, and the Egyptian counter-reformation - Dodson, Aidan (American University in Cairo Press, 2009)
The noonday sun -- The waning sun -- The Northern problem -- The living image of Amun -- The Zananzash Affair -- God's Father to God -- The hawk in festival -- Sunset.